2022
DOI: 10.3390/jintelligence10010017
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Metaverse for Learner-Centered Constructivist Education in the Post-Pandemic Era: An Analysis of Elementary School Students

Abstract: Due to COVID-19, numerous new technologies are being implemented in education, with a growing interest in the metaverse. The term “metaverse” refers to an immersive digital environment where one can interact with virtual avatars. This study aims to analyze the experiences and attitudes of the metaverse for learner-centered education from a constructivist perspective to determine how closely related this virtual environment is to the lives of elementary school students. This study also examined how students are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
1
17

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(128 citation statements)
references
References 34 publications
(35 reference statements)
2
108
1
17
Order By: Relevance
“…Recent studies have confirmed that the use of avatars in virtual reality reduces anxiety in various populations [12][13][14]. While all demographics in studies reported being at ease in engaging with avatars in immersive social environments, introverts, and those with social anxiety disorders, PTSD, and ASD were better able to engage in social virtual reality more effectively than in person [15][16][17][18].…”
Section: Methodsmentioning
confidence: 90%
“…Recent studies have confirmed that the use of avatars in virtual reality reduces anxiety in various populations [12][13][14]. While all demographics in studies reported being at ease in engaging with avatars in immersive social environments, introverts, and those with social anxiety disorders, PTSD, and ASD were better able to engage in social virtual reality more effectively than in person [15][16][17][18].…”
Section: Methodsmentioning
confidence: 90%
“…COVID-19 yang terjadi di berbagai negara termasuk Indonesia berdampak pada berbagai bidang termasuk pendidikan (Sembada et al, 2022). Saat ini dunia pendidikan sedang menghadapi permasalahan yang cukup kompleks (Suh & Ahn, 2022). Serangan virus tersebut berdampak pada penyelenggaraan pembelajaran di semua jenjang pendidikan.…”
Section: Pendahuluanunclassified
“…En cuanto a los espacios de intercambio social en el Metaverso, según el estudio de Suh y Ahn (2022) donde mencionan que, a medida que la tecnología de la comunicación, los gráficos, la computación online, la realidad virtual y las tecnologías de inteligencia artificial se han desarrollado de manera innovadora, se ha vuelto posible configurar un espacio virtual que es similar a la realidad y es factible brindarlo a menor costo. De hecho, durante la pandemia, se realizó el concierto virtual por el músico Lil Nas X en noviembre de 2020 en Roblox, donde se registraron más de 30 millones de espectadores en un total de 4 actuaciones y en abril del 2021, Travis Scott también realizó un concierto virtual en vivo en la plataforma Metaverso Fortnite con 27,7 millones de participantes, incluidas 5 funciones de 10 min cada una (Suh y Ahn, 2022).…”
Section: Introductionunclassified
“…De esta forma, el fenómeno del Metaverso, aparece ya como espacio de segundo orden para compartir actividades sociales, pero bien en corto tiempo podría convertirse en espacio de primer orden que incluso podría reemplazar la realidad misma, dada su continua evolución y desarrollo tecnológico. De los conciertos celebrados en las plataformas de Roblox y Fortnite descritos anteriormente, se publicaron en YouTube las respectivas experiencias en vídeo luego de efectuarse en vivo, obteniendo millones de vistas y reacciones por sus audiencias en esta plataforma de vídeos (Suh y Ahn, 2022). YouTube se encuentra en el primer lugar dentro de la categoría de arte y entretenimiento por TV y películas, y segundo en el ranking global, sólo superado por el buscador de Google.…”
Section: Introductionunclassified